Análise do efeito do distanciamento social nos níveis de emprego setorial - Teixeira, Simone Matos dos Santos (Universidade do Vale do Rio dos Sinos, 2021)
This research aimed to analyze the effect of social distancing on sectoral employment levels in Brazilian States in the year of 2020. The databases were composed by the sectoral employment stock (CNAE 2.0, in 03 digits) in Brazilian States (26 States and the Federal District), the database used to survey the employment stock in the years 2018-2019 was RAIS, a database of employment stock in 2020-2021 was requested from the Ministery of Economy through the SIC. The Shift-share Model was used in the data analysis in order to verify the dynamics of sectors in employment levels and capture the distancing effect on the sectors and regions studied. The results pointed to sectorial employment higher rates, mainly in commerce sectors and a decrease in sectors associated with public administration. They also highlighted locational advantages in the states of São Paulo, Paraná, Santa Cataria and Rio Grande do Sul which, despite high isolation rates in the first half of 2020, achieved positive results in sectorial employment.
Keywords: Covid-19; Emprego; Modelo estrutural-diferencial; Employment; Shift-share; ACCNPQ::Ciências Sociais Aplicadas::Economia